Background Levels of Salivary‐α‐amylase Plus Foreign DNA in Cases of Oral Intercourse: a Female Perspective. Issue 6 (26th July 2015) - Breathnach, Michelle; Moore, Elizabeth
Abstract: Saliva plus DNA from a suspect is commonly encountered in sexual assault cases on bodily swabs. However, without background knowledge, the weight of this evidence is unknown. It may indicate the presence of saliva resulting from cunnilingus, or it may represent indirect transfer. In this study, females who refrained from cunnilingus donated 43 items of underwear and 19 vaginal swabs. The samples were subjected to Phadebas ®, RSID ™ ‐Saliva and mRNA profiling and were subsequently DNA‐profiled to determine the prevalence of background saliva in the female population. The results report that 15.8% of females who refrained from cunnilingus were positive for saliva and a further 10.5% also had DNA from unknown source(s). These findings of the rate of indirect transfer were evaluated with the Bayesian approach, and it was found that the evidence of saliva plus a high foreign DNA source adds moderately strong support to the allegation of cunnilingus.